Pengembangan Agrowisata dalam Rangka Mendukung Pembangunan Pertanian di Kabupaten Ngada, Provinsi Nusa Tenggara Timur - Azi, Paulus Yanuarius; Kaleka, Marten Umbu; Meo, Monika Moe (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Agrotourism is a combination of tourism and agriculture by utilizing existing resources for tourism purposes. This study aims to examine the potential for agrotourism development in Ngada Regency based on regional potential and to determine the development pattern with the agrotourism system. This study is a literature study that collects study materials sourced from previous research results, examines them, examines them and then draws conclusions. The results of the study indicate that Ngada Regency has potential objects for agrotourism development. Several areas that are quite potential in the development of agrotourism in agricultural development efforts are Bajawa, Golewa and South Golewa Districts. Potential objects that can be used as agrotourism are Bajawa coffee plantations, Turetogo Bamboo Campus, Soka hot springs, Roda rice fields and Ogi waterfalls located in the three areas. The pattern of agricultural development with the agrotourism system must emphasize sustainability, conservation-based development, community-based development and regional potential-based development so that it is directed and the target achievement of the program is implemented which then contributes to the development of the Ngada Region